2022
DOI: 10.1038/s41420-022-00889-7
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MEG3 up-regulates SIRT6 by ubiquitinating EZH2 and alleviates nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a global health threat. Here, we presented the significant role of a novel signaling axis comprising long non-coding RNA maternally expressed gene 3 (MEG3), enhancer of zeste homolog 2 (EZH2), and sirtuin 6 (SIRT6) in controlling lipid accumulation, inflammation, and the progression of NAFLD. Mice fed with high-fat diet (HFD) were established as in vitro and in vivo NAFLD models, respectively. Lipid accumulation was measured by oil red O staining and assays for trigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…In line with this these studies, Huang et al [ 131 ] showed that the downregulation of MEG3 in in vitro and in vivo models of NAFLD is negatively correlated with lipogenesis-related genes, and that overexpression of MEG3 alleviates lipid overaccumulation in HepG2 cells. The downregulation of MEG3 in two models of NAFLD (free fatty acid-challenged primary hepatocytes and HFD-induced mouse) was also indicated in a more recent study by Zou et al [ 132 ].…”
Section: Emerging Role Of Ncrnas In the Pathogenesis Of Nafldmentioning
confidence: 62%
“…In line with this these studies, Huang et al [ 131 ] showed that the downregulation of MEG3 in in vitro and in vivo models of NAFLD is negatively correlated with lipogenesis-related genes, and that overexpression of MEG3 alleviates lipid overaccumulation in HepG2 cells. The downregulation of MEG3 in two models of NAFLD (free fatty acid-challenged primary hepatocytes and HFD-induced mouse) was also indicated in a more recent study by Zou et al [ 132 ].…”
Section: Emerging Role Of Ncrnas In the Pathogenesis Of Nafldmentioning
confidence: 62%
“…The authors of another study also observed that MEG3 was markedly increased in NASH cirrhosis specimens [ 39 ]. In contrast, Zou et al showed the opposite finding that MEG3 was downregulated in NAFLD and its reduction paralleled the severity of NAFLD [ 40 ]. A possible explanation for this inconsistency might be that the reactivation and induction of MEG3 in NAFLD and NASH patients is likely a compensatory mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Meg3 also promotes oxidative stress and inflammation in non-cancer cells [ 37–39 ]. However, there are other studies showing a protective role of Meg3 against inflammation [ 40 , 41 ]. Here, we showed that up-regulation of Meg3 in UUO kidneys is detrimental as KO of tubular Meg3 suppressed LPS-induced p38 MAPK activation and CCL-2 and CXCL-2 chemokine production.…”
Section: Discussionmentioning
confidence: 99%